TRANSFORMATION OF THE ARABIC LANGUAGE CURRICULUM IN MADRASAH FROM MINISTRY OF RELIGIOUS AFFAIRS REGULATIONS TO TEACHING MODULES: AN ANALYSIS OF CURRICULUM COMPONENT COHERENCE - Melisa Rezi; Yasmadi Yasmadi; Rahmawati Rahmawati; Zulkifli Zulkifli; Vugar Abdullayev (Lingeduca: Journal of Language and Education Studies, 2026)
The transformation of the Arabic language curriculum in Islamic school (madrasah) is not determined solely by regulatory changes, but also by the extent to which these regulations can be translated into coherent teaching materials. This article aims to analyze the transformation of the Arabic language curriculum in madrasah from Ministry of Religious Affairs regulations into teaching modules, with particular emphasis on the coherence of objectives, content, learning processes, evaluation, and value integration. This study employed a qualitative approach using document analysis. The data were drawn from madrasah curriculum regulations, ranging from Permenag Nomor 2 Tahun 2008 to KMA Nomor 1503 Tahun 2025, as well as the Arabic language teaching module for Grade IX at MTsN 2 Payakumbuh. The data were analyzed through reduction, categorization, coherence mapping, and theoretical synthesis. The findings indicate that the Arabic language curriculum has shifted from a structural-grammatical orientation toward learning that is more communicative, contextual, value-based, reflective, and authentic. At the teaching module level, this transformation is reflected in the strengthening of learning outcomes, life-related themes, active learning activities, differentiation, projects, authentic assessment, Rahmatan lil ‘Alamin Student Profile, and Love-Based Curriculum. However, several parts of the module still show an administrative tendency, particularly in the formulation of objectives and assessment. These findings highlight the need to develop Arabic language teaching modules that not only fulfill administrative formats, but also strengthen the relationship among learning outcomes, materials, activities, assessment, and values, so that regulations are manifested as meaningful learning experiences.